(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This work was conducted for the development of a 5-combi lateral flow immunochromatographic kit (LFK) for rapid and simultaneous identification of the common bacterial causes of bovine mastitis. The following pathogens are the identification targets of this kit: Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Streptococcus agalactiae, and Streptococcus pyogenes in milk samples from suspected bovine mastitis cases. The conventional microbiological identification of these agents is not only time-consuming and requires a fully equipped laboratory but also requires experienced personnel. Materials and Methods: Rabbit polyclonal antibodies (PAbs) specific to the antigenic components of the selected pathogens were prepared, and the pathogen-specific IgG was separated, purified, and conjugated with nanogold that was laid on the conjugate pad. Guinea pig PAbs specific to the microbial antigens of the selected pathogens were prepared, and their IgG content was separated, purified, and used as a capture antibody in the test (T) line on the nitrocellulose (NC) strips. Goat anti-rabbit IgG antibodies were used to capture the rabbit antibodies in the control (C) line of NC strips. The kit was held in a device comprising five strip-holding channels for the abovementioned five bacterial species antigens. The developed LFK was evaluated, and its sensitivity and specificity were determined. Results: The developed kits were applied for the examination of bovine milk samples from suspected mastitis cases, and the average sensitivity, specificity, and accuracy of 5-combi LFK for the detection of the five selected bacterial species compared to bacteriological examination (gold standard test) were 93.90%, 80.83%, and 90.53%, respectively. The minimal microbial count that gave positive results using the developed LFK was 103 colony forming unit/ml. Treatment of the milk samples with an application buffer and its pre-incubation in trypticase soy broth for 6 h at 37°C before testing significantly increased the sensitivity of the prepared LFK. The developed kit proved simple and convenient, and the results could be obtained in less than 10 min. J. Adv. Vet. Anim. Res., 10(2): 292–300, June 2023 http://doi.org/10.5455/javar.2023.j681